SALES PROMOTION AS A FUNCTION IN MERCHANDISING - Vidović, Aleksandra (Časopis za Ekonomiju i Tržišne Komunikacije, 2019)
Behavior of consumers consists of a series of psychological and physical activities in individual process of selecting, purchasing and consuming the products. The purpose and scope of this paper is to investigate the essence of aspects and functions by which merchandising affects the improvement of business in retail environments. The aim of this paper is to determine to what extent the proper product positioning has a direct impact on the improvement of sales results, as well as how to draw attention to a particular product in addition to large number of competing products. On the basis of the aforementioned subject of research, this research presents the possibility of organizing merchandising activities as a kind of cooperation between producers and traders. The research was carried out in such a way that the following hypothesis can be examined on the selected sample: H0- that consumers make the purchasing decision within a moment, which means in front of the shelves where the products are exposed, as well as the auxiliary hypothesis H1- the introduction of a mercantile system into the modern retail business facilities influences the increase in the company’s business results. After the completion of the survey research, the empirical data were processed by the statistical program package for social sciences SPSS 22 and StatPlus 2009.